Monitoring the agri-food system in Myanmar: Agricultural crop traders – June 2024 survey - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
To document changes in the mid-stream of Myanmar’s food value chains, a phone survey of commodity traders was conducted in June 2024 with a sample of 187 active traders in 12 states and regions.